Mengukur transparansi pengelolaan keuangan daerah di Indonesia: berbasis website - Irwan Taufiq Ritonga; Syamsul Syahrir (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2016)
This study aims to measure the transparency of local financial management in Indonesia by focusing on three main stages (aspects) of local financial management, namely the aspects of planning, implementation, and reporting and accountability of the budget. In addition, this study also aimed to cover up the limitations of previous studies that measure the transparency of local financial management. This research was conducted in 34 provincial governments in Indonesia. The data used is the local financial management of the fiscal year 2016. Observations and data collection commenced on November 1 to 31, 2016 for the first period and the second period began in 1-10 January 2017. The second period carried out to check the availability of the data on the provincial government's official website. Based on observations, it was found that the average level of local transparency management is still very small (low), which is equal to 16.84%. The highest-ranking provincial government is a Provincial Government of Central Java with an index of 50% and the lowest is the Provincial Government of Southeast Sulawesi, Provincial Government of West Sulawesi, Provincial Government of North Maluku, and Provincial Government of West Papua with the index transparency of local financial management respectively of 3.45%.